Bolehkah Bercerai?: Melihat Kembali Pandangan Yesus Tentang Perceraian Dalam Matius 19:9 Dengan Pendekatan Kritik Tata Bahasa - Andre Rollando (STT Pelita Dunia, 2023)
Abstract: Whether or not it is permissible to divorce in marriage is still being debated among interpreters when reading the Gospel of Matthew 19:9, and in general Christians see the text as legitimacy for divorce, especially in the phrase